A preference-based comparison of select over-the-top video streaming platforms with picture fuzzy information. (6th May 2022) - Biswas, Sanjib; Pamucar, Dragan; Kar, Samarjit
Over the last few decades, the media industry has witnessed a paradigm shift. Gradually, with massive developments in information and telecommunication technology, the over-the-top (OTT) platforms have emerged as a widely accepted substitute for televisions. The present paper aims to focus on a list of popular OTT platforms in India and carry out a comparative analysis of their acceptability to the consumers in the market. For this purpose, this paper presents a novel extension of the hybrid full consistency method (FUCOM)-multi-attributive border approximation area comparison (MABAC) framework using actual score measures of picture fuzzy (PF) information for multi-criteria decision making (MCDM). We use the framework of quality of experience (QoE) for deriving the attributes. It is observed that the consumers give more importance on viewing experience, convenience and popularity aspects while Amazon Prime, Netflix and Disney+Hotstar are found as better choices to the regular viewers. The result shows consistency and stability.